Multiple doses of sclerostin antibody romosozumab in healthy men and postmenopausal women with low bone mass: A randomized, double‐blind, placebo‐controlled study. (11th December 2013) - Padhi, Desmond; Allison, Mark; Kivitz, Alan J.; Gutierrez, Maria J.; Stouch, Brian; Wang, Christine; Jang, Graham
Abstract Romosozumab (formerly AMG 785/CDP7851) is a monoclonal antibody that blocks sclerostin from inhibiting osteoblast maturation and function. This double‐blind, placebo‐controlled, randomized, ascending multiple‐dose study enrolled 32 postmenopausal women and 16 healthy men with low bone mass. Women received six doses of 1 or 2 mg/kg once every 2 weeks (Q2W) or three doses of 2 or 3 mg/kg once every 4 weeks (Q4W) or placebo; and men received 1 mg/kg Q2W or 3 mg/kg Q4W or placebo. Mean serum romosozumab exposures increased approximately dose‐proportionally. Romosozumab increased serum type 1 aminoterminal propeptide (PINP) by 66–147%, decreased serum C‐telopeptide (sCTX) by 15–50%, and increased lumbar spine bone mineral density by 4–7%. Two subjects developed neutralizing antibodies without discernable effects on pharmacokinetics, pharmacodynamics, or safety. Adverse event rates were balanced between groups without any significant safety findings. These data support continued investigation of sclerostin inhibition in disorders that could benefit from increased bone formation.